IMPROVING STUDENTS' WRITING OF REPORT TEXTS USING ISO TEXT MODELING STRATEGY: MENINGKATKAN PENULISAN TEKS LAPORAN SISWA MENGGUNAKAN STRATEGI PEMODELAN TEKS ISO - Joko Wibowo (IAI Al-Qolam, 2021)
The teaching of writing in Indonesia is aimed at developing writing communicative competence and spoken as well. Furthermore, the coverage of teaching writing is that the students are expected to be competent in creating functional short texts, monolog texts, and essay texts in the forms of genre-based texts. Due to the importance and lack of writing skills of students, this study was performed to solve the students’ problems in writing and encourage students to actively participate in the teaching-learning process through ISO Text Modeling strategy. The findings of the research revealed that ISO Text Modeling strategy was effective to improve the students’ writing skills, especially sorting, selecting, and organizing information skills, and activate students to participate in the teaching-learning process of writing. Key Words: ISO Text Modeling strategy, writing skills